Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/nar/gkv1151
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 binding protein 1 (HspBP1) suppresses HIV-1 replication by inhibiting NF-κB mediated activation of viral gene expression

Abstract: HIV-1 efficiently hijacks host cellular machinery and exploits a plethora of host–viral interactions for its successful survival. Identifying host factors that affect susceptibility or resistance to HIV-1 may offer a promising therapeutic strategy against HIV-1. Previously, we have reported that heat shock proteins, HSP40 and HSP70 reciprocally regulate HIV-1 gene-expression and replication. In the present study, we have identified HSP70 binding protein 1 (HspBP1) as a host-intrinsic inhibitor of HIV-1. HspBP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 66 publications
3
28
0
Order By: Relevance
“…Also involved in regulating apoptosis in infected cells, HSPA1B was shown to inhibit apoptosis induced by the HIV-1 protein Vpr 49 . Consistent with the observed DDX3-mediated induction of NF-κB, HSPA1B was also shown to inhibit HIV-1 reactivation via suppression of NF-κB signalling 50 . RK-33 and FH-1321-mediated downregulation of BIRC5 and RK-33-mediated HSPA1B downregulation was confirmed by RT-qPCR in six additional donor CD4+ T cells ( Fig.…”
Section: Ddx3 Inhibition Downregulates Genes Involved In Cell Survivalsupporting
confidence: 76%
“…Also involved in regulating apoptosis in infected cells, HSPA1B was shown to inhibit apoptosis induced by the HIV-1 protein Vpr 49 . Consistent with the observed DDX3-mediated induction of NF-κB, HSPA1B was also shown to inhibit HIV-1 reactivation via suppression of NF-κB signalling 50 . RK-33 and FH-1321-mediated downregulation of BIRC5 and RK-33-mediated HSPA1B downregulation was confirmed by RT-qPCR in six additional donor CD4+ T cells ( Fig.…”
Section: Ddx3 Inhibition Downregulates Genes Involved In Cell Survivalsupporting
confidence: 76%
“…While several host factors aggravate or diminish HIV-1 mediated effects in the body, we focused our study on mortalin, a member of the heat shock protein 70 (HSP70) family. Recent studies have shown that HSP70 expression was inversely correlated with viral replication [ 45 ], indicating that this could play an important role in the progression and prevention of the disease manifestation. HIV-1 was also found to decrease the levels of HSP70, and this is also corroborated by our study.…”
Section: Discussionmentioning
confidence: 99%
“…replication by suppressing NF-B-mediated activation of viral transcription (50). Host factor DNAJC14, an Hsp40 chaperone protein family member, inhibits yellow fever virus and hepatitis C virus at the step of viral RNA replication (51).…”
Section: Discussionmentioning
confidence: 99%